Soccer365 MMS Application / Khairul Anwar Zainal - Khairul Anwar, Zainal (2005)
This project documentation describes in detail the information regarding the project Soccer365 on MMS. The first part of this thesis, WXES 3181, is primarily divide into four chapters, that introductions, Literature Review, Methodology and System Design The second part, WXES 3182, consists oh three chapters; System Implementation, System Testing and System Evaluation. Chapter I, Introduction, will give the reader an overview of whats this thesis is all about. Also, the objectives for developing this project the targeted user group, project limitattions, the scope covered by this project and an estimated schedule to finish the project are cleary stated. In Chapter 2, Literature Review, a thorough review on similar existing systems is carried out in order to obtain a better understanding with regards to the proposed project. It provides developers with some knowledge and insights into the strengths and limitations of several development tools that is available in the market. The software and scripting languages best used to develop the project is also researched. In Chapter 3, Methodology, will be discussed the right type of methodology used for completing every activity in the System Development Life Cycle and also the tools to be used for the project. In Chapter 4, System Design, the development of the proposed project will be discussed and ascertained. This includes system functionality design and module functionality design. It shows the modules involved in the system and the data flow when information is passed. In Chapter 5, System Implementation, the system is implemented into a workable system based on the system requirements and design specifications. In Chapter 6, System Testing is broken down into three distinctive phases; unit testing, integration testing and system testing. Some of the methods such a function testing, performance testing, acceptance testing and installation testing were used to facilitate this operation. Finally, in Chapter 7, System Evaluation, the difficulties and problems encountered during the development process from the beginning until the end of the project, the solutions to the problems, the strengths and the limitations of the system being developed, and the future enhancement of the system are thoroughly discussed.